2021
DOI: 10.3390/ma14144042
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Surface Condition and Changes in Crystallographic Structure of Zirconium Oxide Affected by Mechanical Processing

Abstract: Zirconium oxide is a material commonly used in dental prosthetics for making cups of permanent prosthetic restorations. In order to properly prepare the surface of zirconium oxide for prosthetic treatment, it must be veneered with ceramics. The quality of cup-veneered ceramics is dependent on many factors, including the surface free energy (SFE) and transformation of zirconium oxide. The aim of the study was to investigate the type of phase transition and the value of free energy of the surface subjected to ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…The obtained results concerning the milled samples are analogous to the results presented in this paper. In the sample after the milling process [30], no tetragonal phase was found either. The lack of this phase can also be explained by the fact that the milling process is followed by the sintering process, and at the temperature at which it takes place, the tetragonal phase is the stable phase.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The obtained results concerning the milled samples are analogous to the results presented in this paper. In the sample after the milling process [30], no tetragonal phase was found either. The lack of this phase can also be explained by the fact that the milling process is followed by the sintering process, and at the temperature at which it takes place, the tetragonal phase is the stable phase.…”
Section: Discussionmentioning
confidence: 85%
“…Diffractometric examinations have shown that the abrasive blasting of zirconium oxide causes a transformation from the tetragonal phase into a monoclinic phase in its surface layer. By analyzing the amount of the monoclinic phase after blasting in relation to the amount of this phase after grinding (presented for the same material in [30]), it can be concluded that abrasive blasting increases the degree of transformation in relation to grinding. This is due to the greater aggressiveness of this treatment related to the greater energy that the abrasive grains have in the air stream in relation to the energy of the grains in the abrasive elements.…”
Section: Discussionmentioning
confidence: 99%
“…The developed prosthetics and computer methods cause the CAD/CAM technology connected with milling to be more and more popular and frequent. The method is very precise: the edge tightness is of the order of 30 µm, compared to the generally acceptable tightness for the fixed prosthetic structures of 100 µm [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…An ideal, all-ceramic dental material should be characterized by excellent aesthetic properties, such as translucency, transparency, color as close as possible to one’s own teeth, and the highest values of mechanical properties in order to be able to use it for many years. Until now, zirconium oxide was considered the best choice, and it has the lowest plaque accumulation value compared to other prosthetic restorations [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that meeting these requirements was possible through the use of a new method and new tools. Conclusions came from the resent investigations on the features of abrasive tools [3,8,19,20], process kinematics [21], the influence of the processed material properties on the process results [22][23][24][25][26] and cutting fluid [9,27]. In the assumptions for the new method, the developed methodology of process monitoring [28,29], a thorough analysis of the properties of abrasive tools [30][31][32], and the topography of the treated surfaces [33] were used.…”
Section: Introductionmentioning
confidence: 99%